Increase in average crop and leanness of eucalyptus (Eucalyptus Pelita) at Pt Itci Hutani Manunggal, Kutai Kartanegara Regency - Kamarubayana, Legowo; Yahaya, Zuhdi; Hasanuddin, Hasanuddin (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The purpose of this study was to determine the slenderness and current annual increment) both in diameter and height of the area. The expected results of this study can provide information about plant leanness and plant growth in Ekaliptus (Eucalyptus pelita) at PT ITCI Hutani Manunggal Kutai Kartanegara Regency. Also, as a consideration in determining the type of plant that is suitable for or better for growth than plants Ekaliptus (Eucalyptus pelita), both at the planting site used for this research and at other locations. The sample used in this study was 40 trees in a purposive way. Height measurement tools use the Haglof vertex, while diameter measurement tools use the phi band. The results of measuring the dimensions of 40 Eucalyptus plants at PT. ITCI Manunggal Hutani Kutai Kertanegara Regency shows that the average height is 13.38 m with a coefficient of variation of 16.37%, while the average diameter measurement is 10.04 cm with a coefficient of variation of 24.37%. The average increase in height is 4.48 m, and the average increase in diameter is 3.35 cm. Plant Ekaliptus (Eucalyptus pelita) growth between diameter and height has unstable slenderness